Gestão de línguas em ambiente empresarial fronteiriço: um estudo de caso na Itaipu Binacional - Fonseca, Lívia Cristina Carvalho da (2020)
This research has as theme the language management in a border working environment and has as scenario the Itaipu Binacional hydroelectric power plant, located in the border between Brazil and Paraguay. Built in the 1970s and completed in 2007, the power plant, the world's largest power generator, has Brazilian and Paraguayan employees, who are part of the multilingual context of the trinational border of Foz do Iguaçu (Brazil), Ciudad del Este (Paraguay) and Puerto Iguazú (Argentina). In order to contribute to Language Policy research in border regions (BERGER, 2015; FIAMENGUI, 2017; DAY, 2013) and to fill a gap on workplace language management studies, developed mainly in the northern hemisphere (ANGOURI, 2013; LADEGAARD; JENKS, 2015; VAN DER WORP; CENOZ; GORTER, 2018), we looked at the language management policies and actions at Itaipu Binacional. In a case study, we investigated the practices, linguistic attitudes and management strategies of multi/plurilingualism adopted by employees of the MEG-1 sector, using Spolsky's model (2004; 2009) as a theoretical input for the analysis of language policies. For this purpose, methodological procedures were adopted such as the documental analysis of the plant's official guidelines that regulates the use of languages; the observation of the linguistic practices of Brazilian and Paraguayan workers within the MEG-1 framework; and the application of questionnaires to Brazilian employees seeking to understand their perceptions regarding the linguistic policies and practices adopted in the work environment, as well as their attitudes towards the languages circulating in the company and sector. In conclusion, it was understood that the company's language policies, since its foundation, have guided that the official languages are Portuguese and Spanish and they instruct only with regard to written communication and the company’s linguistic landscape. In the daily work practices of MEG-1 employees, the intercomprehension of Latin languages was observed as an effective communication strategy between Paraguayans and Brazilians, although in the perception of the respondents of the questionnaire common sense prevails and they believe that portunhol is in fact the tool used in oral practices among employees. Regarding the respondents' attitudes towards the Portuguese, Spanish and Guarani languages, the answers were neutral. This survey falls within the field of Linguistic Policy research and it is pertinent because it covers issues that are of interest in the scope of multi/plurilingualism management surveys in border regions and reveals strategies for managing linguistic interactions in the work environment peculiar to the Latin American context, highlighting actions that may be taken into consideration in future studies.